MANFAAT SUSENAS (Survei Sosial Ekonomi Nasional) DALAM PEMBANGUNAN MASYARAKAT KABUPATEN SUKABUMI - Apriliyanti, Silvi; Kharisma, Ivana Lucia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Data collection on the social and economic conditions of the comummunity is an activity carried out by the government to deremine the percentage og the poor population, school participation rates, and household expenditures. The cental Bureau of Statistics (BPS) conducts a program twice a year called the National Socioeconomic Survey (Susenas). In its implementation, Susenas uses the Paper and Pencil Interviewing (PAPI) method where the BPS team directly visits selected households as respondents to be interviewed according to the provided question template. There are two questionnaires used: first,related to education and employment. Second, household expenditure and consumtion. The results of the implemented Susenas provide an overview of the the indicators of people’s welfare, which is expeted to make future development planning more targeted and more responsive to the needs of the general public, so that in turn, the quality of life of the people of Sukabumi Regency through government policies referring to the results of Susenas will continue to improve along with the development of the region.